A review on upcycling waste cooking oil into polyhydroxyalkanoates (bioplastic): a pathway for sustainable material - Bhatia, Shashi Kant; Patel, Anil Kumar; Saratale, Ganesh Dattatraya; Kumar, Vinod; Yang, Yung-Hun (Elsevier, 2025)
Waste cooking oil (WCO) improper disposal leads to water pollution, ecosystem disruption, and human health hazards. Various upcycling strategies have been explored, including conversion to biodiesel, surfactants, and biodegradable polymers. Converting WCO into polyhydroxyalkanoates (PHAs), biodegradable and biocompatible bioplastics, offers a sustainable solution aligned with circular economy principles. WCO usually requires minimal or no pretreatment and can be effectively used as a carbon source for microbial fermentation. Free fatty acids (FFAs) from WCO are readily metabolized by PHA producing bacteria such as Cupriavidus necator and Pseudomonas spp., enabling PHA accumulation ranging from 27 % to 96 % (w/w). Depending on the microbial strain and fermentation strategy, both short chain length (scl-PHA) and medium chain length (mcl-PHA) polymers with varied properties can be synthesized. The coproduction of other products, such as carotenoids and surfactants, may further improve the process economics. However, variability in the composition of various oils can cause inconsistent productivity and monomer distribution, highlighting the need for thorough feedstock characterization. Insights from recent studies highlight that oils rich in long chain unsaturated fatty acids (LCFA), such as rapeseed or canola oil, enable the highest biomass and PHA yields, while oils dominated by medium chain saturated fatty acids (MCFA) favor flexible mcl-PHAs but with lower productivity. Integrating artificial intelligence (AI) and machine learning could further improve predictive analysis, process control, and strain selection. This review emphasizes the importance of aligning feedstock composition, microbial selection, coproduction, and improved fermentation strategies to advance sustainable PHA production from WCO.
Keywords: 31 Biological Sciences; 3106 Industrial Biotechnology; Machine Learning and Artificial Intelligence; 12 Responsible Consumption and Production; Polymers; 3101 Biochemistry and cell biology; Biodegradable; Polyhydroxyalkanoates; Waste cooking oil; Circular economy; Artificial intelligence